Synthesis And Characterization Of New Metals Complexes Of [N-(acetyl amino) Thioxomethyl] Valine - Kindeel, Alia S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new ligand [N-(acetyl amino) thioxomethyl] valine was prepared from the reaction of acetyl iso thiocyanate with valine. The ligand was characterized by FT-IR, UV- vis and 1HNMR spectrum, The complexes with some metal ions (M +2 =Co,Ni,Cu,Zn,Cd,Hg) have been prepared and characterized. The structural diagnosis were established by IR,UV-Vis spectrum, flame atomic absorption spectroscopy conductivity and magnetic susceptibility ,the complexes showed tetrahedral geometry around the metal l.